SUBTITUSI BUBUK BIJI SALAK DAN BUBUK KOPI ARABIKA DALAM PEMBUATAN BUBUK KOPI - Lestari, Devi; Kadirman, Kadirman; Patang, Patang (Jurnal Pendidikan Teknologi Pertanian, 2017)
This research aims to find out the possibility of substitution seed powder of salak and arabica coffee powder to be used as an alternative the coffee powder and comparison of seed powder of salak and arabica coffee powder to most panelist favored. The observed parameters proximate test namely carbohydrates, protein, moisture content, ash content, caffeine content, and organoleptic test, which consists of color, scent of and flavor. Research results show that the substitution seed powder of salak to arabica coffee powder is enabling do the mixing, based on test results hedonic which consists of color, scent of and flavor shows the average value of 6,12-7,31 which mean decent and the best treatment lies in the A treatment (25% seed powder of salak and 75% Arabika coffee powder). Proximate of test results showed the highest carbohydrate content lies on D treatment (100% seed powder of salak), while the highest protein content lies on the K treatment (100% Arabica coffee powder), fhurthermore the lowest ash content and the lowest caffeine levels is contained on the D treatment and low water content is contained on the K treatment